2022
DOI: 10.1002/smi.3139
|View full text |Cite
|
Sign up to set email alerts
|

Suffering, psychological distress, and well‐being in Indonesia: A prospective cohort study

Abstract: Research on the subjective experience of suffering has typically focussed on older clinical samples living in Western, educated, industrialised, rich, and democratic (WEIRD) countries. To further extend the existing body of empirical research on suffering to less WEIRD contexts, we use three waves of data (Wave 1: December 2020; Wave 2: January 2021; Wave 3: February 2021) from a sample of nonclinical Indonesian adults (n = 594) to examine associations between suffering, two indices of psychological distress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 64 publications
(83 reference statements)
5
19
0
Order By: Relevance
“…This general theory suggests that a fully happy brain (Breuning, 2015), even in times of suffering, depend on developing the wisdom of the soul (McLaughlin & McMinn, 2022;Siegal, 2018;Vaillant, 1998). My parting thought is that we really need more research to discover why people have the uncanny propensity and ability to turn heaven into hell, and to create hell for themselves for no apparent reasons (Cowden et al, 2021;Ho et al, 2022). The general theory of mental health and wellbeing is to enable people to live the best possible bittersweet life (Cain, 2022) of turning hell into heaven and preventing the self-destructive act of turning heaven into hell.…”
Section: Discussionmentioning
confidence: 99%
“…This general theory suggests that a fully happy brain (Breuning, 2015), even in times of suffering, depend on developing the wisdom of the soul (McLaughlin & McMinn, 2022;Siegal, 2018;Vaillant, 1998). My parting thought is that we really need more research to discover why people have the uncanny propensity and ability to turn heaven into hell, and to create hell for themselves for no apparent reasons (Cowden et al, 2021;Ho et al, 2022). The general theory of mental health and wellbeing is to enable people to live the best possible bittersweet life (Cain, 2022) of turning hell into heaven and preventing the self-destructive act of turning heaven into hell.…”
Section: Discussionmentioning
confidence: 99%
“…Each item is rated using an 11-point response scale, with different anchor points for the first item (0 = Not suffering at all ; 10 = Suffering terribly ) compared to the other six items (0 = Strongly disagree ; 10 = Strongly agree ). Consistent with previous research (e.g., Cowden et al, 2021 , 2022 ; Ho et al, 2022 ), responses to the items were averaged for an overall suffering score.…”
Section: Methodsmentioning
confidence: 98%
“…The T 2 and T 3 surveys contained the same set of measures that were administered at T 1 . A masked translation and back-translation process was used to translate the surveys from English to Indonesian (for further details, see Ho et al, 2022 ); all participants completed the surveys in the Indonesian language. Participants were compensated the equivalent of $6 (USD) for participating in the three surveys.…”
Section: Methodsmentioning
confidence: 99%
“…However, the findings of previous studies provide little evidence in alignment with this notion. Effect sizes reported in a number of prior cross-sectional studies suggest a small-to-moderate positive association between depression and suffering (e.g., Büchi et al, 2002;Brady et al, 2019;Davis et al, 2021), with slightly smaller effect sizes found in a few longitudinal studies that have been conducted (e.g., Cowden et al, 2021b;Ho et al, 2022).…”
Section: Empirical Evidence Distinguishing Depression and Sufferingmentioning
confidence: 98%
“…To date, much of the research on suffering has focused on clinical samples comprising older adults who are experiencing physical health symptoms (e.g., pain), have chronic medical illnesses (e.g., cancer), or are receiving palliative care ( Cowden et al, 2021b ). However, recent research has documented the potential for suffering to degrade well-being among non-clinical young adult populations (see Ho et al, 2022 ), suggesting that further consideration should be given to the implications of suffering for the functioning of both clinical and non-clinical populations. Broadening the scope of research on suffering to a more diverse range of populations could enhance our understanding about the nature of suffering, its linkages to other related constructs (e.g., depression), and how it might be effectively addressed to promote well-being.…”
Section: Introductionmentioning
confidence: 99%